The Impact of Digital Economy in Driving Economic Growth and Development in Indonesia - Sofi Meidyasari (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The digital economy has been proven to have a significant impact on economic growth and national development in Indonesia, and with effective management, the digital economy can become a key driver of economic growth in the future. This research aims to analyze the impact of digital economic transformation on Indonesia's economy, focusing on how digital technology can improve productivity, innovation, and market access for various sectors. Data were collected from various relevant sources, including journals, government reports, articles, and case studies. The qualitative method combined with the literature review and triangulation approach facilitated an in-depth understanding of the complex and evolving dynamics of digital economy in Indonesia. The study aimed to provide nuanced insights and actionable policy recommendations to support the sustainable development of the Indonesian digital economy. Through a comprehensive approach, this research could explore access to digital tools, funding, and training as critical elements for MSME success in the digital era.